2013
DOI: 10.2106/jbjs.k.01682
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Short-Term Complications Between Spinal and General Anesthesia for Primary Total Knee Arthroplasty

Abstract: Patients undergoing total knee arthroplasty who were managed with general anesthesia had a small but significant increase in the risk of complications as compared with patients who were managed with spinal anesthesia; the difference was greatest for patients with multiple comorbidities. Surgeons who perform knee arthroplasty may consider spinal anesthesia for patients with comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
214
6
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(229 citation statements)
references
References 18 publications
5
214
6
4
Order By: Relevance
“…Despite the potential applications of the current ACS NSQIP database, research has shown that surgeons remain skeptical on publically reporting ACS NSQIP data and applying it beyond the institutional level [13]. In fact, only a few orthopaedic surgical studies have already employed the NSQIP database [2,12,15,16,21,22]. These studies limited their analysis to either single orthopaedic procedures or reported rates of adverse events without considering the effect of patient characteristics and comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential applications of the current ACS NSQIP database, research has shown that surgeons remain skeptical on publically reporting ACS NSQIP data and applying it beyond the institutional level [13]. In fact, only a few orthopaedic surgical studies have already employed the NSQIP database [2,12,15,16,21,22]. These studies limited their analysis to either single orthopaedic procedures or reported rates of adverse events without considering the effect of patient characteristics and comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…4 In 2013, Pugely et al studied the American College of Surgeons National Surgical Quality Improvement Program database and showed that patients who had undergone primary total knee replacement with spinal anesthesia had shorter LOS than those who had been given GA (3.45 vs 3.77 days). 8 Memtsoundis et al reported similar findings after studying data from a large US database. 7 In our study, patients in the NA group had shorter LOS than those in the GA group, confirming that the findings noted in the North American health systems were similar to those from Asia.…”
Section: Discussionmentioning
confidence: 69%
“…Nous avons créé deux sous-groupes appariés par score de propension, chacun incluant un nombre égal de patients ayant subi une AT sous AG ou AN. (8 [7-10] jours contre 8 [6][7][8][9][10] jours; P = 0,024). Conclusions Nos résultats sont en faveur de l'utilisation de l'AN pour les AT de première intention.…”
Section: Résuméunclassified
See 1 more Smart Citation
“…A common approach is to divide subjects into five equal-size groups or strata using the quintiles of the estimated propensity score. The study by Pugely et al [18] of the effect of general versus spinal anesthesia on short-term complication risk after primary total knee arthroplasty is an example of using stratification on propensity scores quintiles to adjust their estimates for the effect of group imbalances. A treatment effect can be estimated in each strata (cases with similar propensity score will have comparable covariate profiles), then combined across strata using weights to obtain an overall estimate.…”
Section: How Are Propensity Scores Used?mentioning
confidence: 99%